David Stuttard. Greek mythology: a traveller’s guide from Mount Olympus to Troy - Vos, Gary (Journal of Greek Archaeology, 2016)
Is there anything new to be said about classical mythology? Recent decades have seen a flurry of encyclopaedias, overviews of and introductions to the subject, and monographs on specific figures or themes. Any author wishing to enter the fray must, I imagine, suppress some queasiness at such competition. Not so David Stuttard (hereafter ‘S.’). S.’s book is of a very different kind and is perhaps best described as a Pausanias for our times. S. is a gifted and prolific populariser of Classics, renowned for (co)authoring and editing over a dozen books on various aspects of Classical civilization and producing a further dozen translations, half a dozen adaptations, and many a staging of Greek dramas. Greek Mythology is a perfect addition to his oeuvre. The dust jacket promises that this book is ‘[t]he perfect companion to the Greek myths and the landscapes and ideas that shaped them.’ As the introduction (12–13) and dust jacket freely admit, it is aimed at real and armchair travellers alike (the quality of the cover suggests the second category is the majority of the envisioned readership). While not written for the specialist, the book may be of interest to (armchair) scholars as well.